PERSPEKTIF HUKUM PERPAJAKAN TERHADAP PENAGIHAN PAJAK ATAS BPHTB YANG KURANG DIBAYAR OLEH WAJIB PAJAK DI MEDAN - FRINAN SATRIA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Bastari3. Jelly Leviza Tax is the country’s biggest revenue source so that it plays a vital role in a country. Tax arrears in Indonesia are significant that they require law enforcement by fiscal authorities in collecting tax. The research problems are how the legal certainty is fulfilled in the provisions of collecting system of BPTHB (Duty on Land and Building Right Acquisition) in Medan, how the fiscal authorities and tax collecting for BPTHB that is underpaid by taxpayers. This is a prescriptive normative juridical research. It puts priority to primary legal materials such as the regulations related to tax laws.Keywords: Duty on Land and Building Right Acquisition, Tax Collection, Underpayment, Regency/ Municipal Tax